2013
DOI: 10.1002/ldr.2208
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Maize Growth in Saline and Nonsaline Soils using Cassava‐Industrial Waste Compost and Vermicompost with or Without Earthworms

Abstract: The aim of this study was to investigate the effectiveness of compost and vermicompost as soil conditioners in alleviating salt‐affected soils and increasing maize productivity. A greenhouse trial, consisting of seven soil amendment treatments in a completely randomized design with three replications, was carried out at Khon Kaen University, Thailand, during the rainy season of 2011. Plant height and total dry matter of maize increased in treatments with compost and vermicompost application when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 54 publications
(56 reference statements)
16
101
0
2
Order By: Relevance
“…The use of the VP amendment aided cucumber fruit yield under continuous cropping conditions. This outcome might result from the excellent physical characteristics and abundant nutrients of VP (Zhao et al 2010a, b;Ravindran et al 2016) and the ability of VP to effectively regulate soil properties (Oo et al 2015).…”
Section: Yield and Quality Responses To Soil Vermicompost Amendmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the VP amendment aided cucumber fruit yield under continuous cropping conditions. This outcome might result from the excellent physical characteristics and abundant nutrients of VP (Zhao et al 2010a, b;Ravindran et al 2016) and the ability of VP to effectively regulate soil properties (Oo et al 2015).…”
Section: Yield and Quality Responses To Soil Vermicompost Amendmentmentioning
confidence: 99%
“…The cause of this effect might be the ability of VP to promote crop system development more effectively than other fertilizers and the capacity to absorb more mineral ions while simultaneously producing hydrogen ions (Edwards and Burrows 1988;Orozco et al 1996). The unique characteristics of VP and the beneficial interaction between VP and soil (Ngo et al 2012;Oo et al 2015) suggest that VP amendments could significantly increase soil water-holding capacity and lower bulk density, which is conducive to the healthy growth of crops. The nitrogen characteristics of soil directly reflect its fertility, and influence the absorption and utilization of mineral elements by plants.…”
Section: Effects Of Vermicompost Application On Soil Propertiesmentioning
confidence: 99%
“…Salt affected soils generally exhibit poor structural stability due to low organic matter content. Many researchers have suggested that the structural stability of soil can be improved by the addition of organic materials (Oo et al, 2013). Rice straw and cowdung are the farm products which can be used for reclamation of saline soils as it offers an opportunity to improve the physical conditions of the soil and also to some extent improves soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Their design aims to minimise drainage into underlying hazardous wastes. Contrary to conventional covers made of compacted clay, geosynthetic clay liners, or polyvinyl chloride (Othman et al, 1994;Benson, 2000;Levin and Hammod, 1990), phytocaps serve two purposes: (1) to maximise rainfall interception by vegetation and, if required, a compacted soil layer, and (2) to remove soil water through plant transpiration and evaporation from bare soil (Salt et al, 2011). Through successive rainfall events, the loss of stored soil water through evapotranspiration decreases net percolation through the soil (Hauser et al, 2001;Rock, 2010) and reduces surface runoff and erosion.…”
Section: Socio-ecological Impacts Of Open-cut Miningmentioning
confidence: 99%
“…Typically, the impact of macrofauna (e.g. ants, termites, earthworms) on soil structure is scarcely recognised by these ecological engineers and soil scientists, despite recognition by soil ecologists and entomologists that the soil macrofauna significantly contributes to ecosystem services such as soil formation, water availability for vegetation, or flood and erosion control (Lavelle et al, 2006;Cerdà et al, 2009;Cerda and Jurgensen 2011), and soil development and fertility (Oo et al, 2013;Bottinelli et al, 2015). This omission of macrofauna from landscape design may in part be due to the current lack of quantitative knowledge of their role in the nature and timing of significant alterations to soil physical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%